Oxidation-driven self-assembly gives access to high-nuclearity molecular copper vanadium oxide clusters - Forster, Johannes; Rösner, Benedikt; Fink, Rainer; Nye, Leanne; Ivanovic-Burmazovic, Ivana; Kastner, Katharina; Tucher, Johannes; Streb, Carsten (Chemical Science, 2013)
We report a general fragmentation-and-re-assembly route which gives access to high-nuclearity, mixed-metal polyoxometalate clusters. Reduced vanadium(iv) precursors are oxidatively dis-assembled into reactive fragments which subsequently re-aggregate under template control in a one-pot reaction. It is shown that the oxidative dis-assembly is required, as the use of vanadium(v)-based precursors results in the formation of smaller clusters. The principle is exemplified by the synthesis of a ca. 1.8 × 1.7 × 1.0 nm, 36-nuclear copper vanadium oxide cluster, (nBu N)[CuVO(NO )(CHCN)]. The cluster is characterized in the solid-state and in solution by single-crystal XRD, ESI-MS and other spectroscopic and electrochemical measurements. Several lines of evidence show that the compound is indeed formed exclusively by fully oxidized vanadium(v) centres. In addition, primary fragmentation products of the type [VO(dmso)] were isolated. The cuprovanadate cluster features pentagonal secondary building units of the type (V)M (M = Cu, V) which show similar structural function as the well-known (Mo)Mo pentagons observed in giant molybdate clusters. The observation suggests that more complex vanadate clusters might be accessible based on these pentagonal units. © 2013 The Royal Society of Chemistry.

Tuning the light absorption of a molecular vanadium oxide system for enhanced photooxidation performance - Forster, Johannes; Rösner, Benedikt; Khusniyarov, Marat; Streb, Carsten (Chemical Communications, 2011)